1954
DOI: 10.1113/jphysiol.1954.sp005195
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal absorption of amino‐acid enantiomorphs

Abstract: Gibson & Wiseman (1951) showed that when amino-acids were injected into the lumen of the intestine of the rat, the L-enantiomorph disappeared at a faster rate than the D-enantiomorph, and they postulated a stereochemically specific mechanism for the absorption of L-amino-acids. In support of this, Clarke, Gibson, Smyth & Wiseman (1951) showed that L-amino-acids also disappeared faster than D-amino-acids from the Thiry-Vella loop in the dog, and Wiseman (1953) showed with an in vitro technique that L-amino-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1956
1956
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The D-and L-enantiomorphs of methionine and histidine were obtained commercially. As will be shown, Gibson & Wiseman (1951) and Matthews & Smyth (1954) in showing that the L-enantiomorphs are absorbed more rapidly than the corresponding D-forms. The present results, however, give figures for absorption rates when only the L-or D-enantiomorph was present in the intestine, whereas in the other experiments referred to the amino acid was present as the racemic mixture.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The D-and L-enantiomorphs of methionine and histidine were obtained commercially. As will be shown, Gibson & Wiseman (1951) and Matthews & Smyth (1954) in showing that the L-enantiomorphs are absorbed more rapidly than the corresponding D-forms. The present results, however, give figures for absorption rates when only the L-or D-enantiomorph was present in the intestine, whereas in the other experiments referred to the amino acid was present as the racemic mixture.…”
mentioning
confidence: 83%
“…Gibson, Newey, Smyth & Whaler (1954) showed that the capacity for synthesis of some L-amino acids from the corresponding D-enantiomorphs was not present in the intestine to any appreciable extent, although in fact histidine was not one of the amino acids which they tested. Certainly all transfer of D-amino acids does not happen by conversion to the L-amino acid, since Matthews & Smyth (1954) found that D-amino acid appeared in the portal blood when present in the lumen of the intestine.…”
mentioning
confidence: 99%
“…The principle of the method used was that ofMatthews & Smyth (1954) in which the blood draining a loop ofintestine is collected, so that none of the products of absorption entering the blood stream are returned to the animal. In this method, the blood pressure was maintained at a low level in order to reduce the rate of intestinal blood flow.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…GIBSON and WISEMAN (1951) reported that L-forms of amino acids disappeared from intestine of rats more rapidly than their corresponding D-enantiomers and therefore they regarded existence of a stereochemically specific mechanism for active absorption of L-amino acids. Later results (VISEMAN, 1953;AGAR et al, 1953;MATTHEWS and SMYTH, 1954) showed that transport of L-amino acids involves an active process and it was assumed that this did not apply to D-amino acids. On the other hand, JERVIS and SMYTH (1959) showed that competition between some Dhistidine and L-Met was possible using in vivo as well as in vitro techniques (WISEMAN, 1955).…”
Section: Experiments Designmentioning
confidence: 99%